Autobiografia na cztery rece - Giedroyc, Jerzy; Pomian, Krzysztof (Warszawa : Czytelnik, 1994)
An autobiography of a noted Polish periodical editor who settled in France after WW II.
Includes index.
Keywords: Giedroyc, Jerzy; Kultura (Paris, France); Periodical editors -- France -- Biography; Periodical editors -- Poland -- Biography; Polish people -- France -- Biography